2022
DOI: 10.1186/s12888-022-03811-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pattern of vitamin D receptor-associated genes and lncRNAs in patients with bipolar disorder

Abstract: Background Bipolar disorder (BD) is a multifactorial condition. Several signaling pathways affect development of this disorder. With the purpose of exploring the role of vitamin D receptor (VDR) signaling in this disorder, we measured expression of selected mRNA coding genes and long non-coding RNAs (lncRNAs) in this pathway in patients versus normal subjects. Methods We measured expression of VDR-associated lncRNAs and mRNAs (SNHG6, MALAT1, Linc00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Further experiments have shown upregulation of VDR, MALAT1 and LINC00511 in breast tumors relative to nearby non-cancerous samples, and associations between clinicopathological data and expression of VDR-associated lncRNAs [ 48 ]. These lncRNAs have also been examined in Parkinson's disease [ 49 ], bipolar disorder [ 50 ], schizophrenia [ 51 ], and epilepsy [ 52 ].…”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
“…Further experiments have shown upregulation of VDR, MALAT1 and LINC00511 in breast tumors relative to nearby non-cancerous samples, and associations between clinicopathological data and expression of VDR-associated lncRNAs [ 48 ]. These lncRNAs have also been examined in Parkinson's disease [ 49 ], bipolar disorder [ 50 ], schizophrenia [ 51 ], and epilepsy [ 52 ].…”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
“… 38 Because vitamin D receptor polymorphisms also contribute to bipolar disorder, gene polymorphisms may influence both neuroaxonal integrity and the effects of vitamin D on brain function in bipolar disorder. 39 Future longitudinal studies are required to investigate potential temporal associations between these factors. We also analysed the association between vitamin D, NfL levels and the interaction and clinical variables, such as clinical course and DDD, for each pharmacological category.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed higher VDR expression in both dlPFC and ACC in suicides relative to controls [ 99 ]. Another study also reported an upregulation of the VDR gene in bipolar disorder, and it correlated with an elevated risk of premature death from suicide and comorbid conditions [ 116 ]. These changes in the VDR gene expression could be associated to genetic variants or epigenetic factors.…”
Section: Relationship Between Vdr Gene Depression ...mentioning
confidence: 99%